Reconceptualizing the notion of “study” while studying abroad: International students at a Thai university - Na Ranong, Sirirat; Byram, Michael (Journal of International Students, 2025)
This study explores the academic experiences of 14 international students at Thailand’s Faculty of Liberal Arts and how these experiences reshape their concept of “study.” Findings from the interview show that students modified the concept of study after encountering new experiences of teaching and learning, shifting from viewing learning as an individual, lecture-based activity to embracing a collaborative approach. This shift in subjective culture is reflected in material culture, underscoring how these cultural aspects reinforce one another. Overall, the findings challenge the conventional East-West academic culture dichotomy, revealing a blended approach that defies simplistic cultural divides. Also, it demonstrates the applicability of Huber & Reynolds’ (2014) model—which considers material, social and subjective aspects of culture—as a valuable framework for examining academic culture. Though small in scope, this study provides insights into student’s reconceptualisation of “study” in the Southeast Asian context and offers a foundation for future research on academic culture.